2010
DOI: 10.1007/s00106-010-2222-7
|View full text |Cite
|
Sign up to set email alerts
|

Laryngektomierte Stimmprothesenträger

Abstract: Supra-esophageal reflux influences voice quality and quality of life in laryngectomised patients with voice prostheses. This can be explained, for example, by an increased incidence of periprosthetic leakage, the presence of edema in the pharyngo-esophageal segment (where speech is produced), and general reflux symptoms. Rigorous treatment with anti-reflux medications leads to an improvement in reflux parameters that can be assessed objectively (RAI) and in correlated quality of life and voice quality paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…An ample 6 month study from the University of Ulm, under the coordination of K. Lorenz, performed on 60 total laryngectomy patients who had vocal prostheses, analyzed the 24h pHmetry before and after 6 months of PPI therapy. Results showed that patients with supra-esophageal reflux treated with PPI had a 10 times lower risk to develop enlargement of the fistula and the complications that derive from it [23]. Similar results were reported by the teams led by Cocuzza [24] and Pattani [25] the difference being that this paper took into consideration radiotherapywhich was demonstrated to be another independent risk factor in developing complications of tracheoesophageal speech rehabilitation.…”
Section: Resultssupporting
confidence: 80%
“…An ample 6 month study from the University of Ulm, under the coordination of K. Lorenz, performed on 60 total laryngectomy patients who had vocal prostheses, analyzed the 24h pHmetry before and after 6 months of PPI therapy. Results showed that patients with supra-esophageal reflux treated with PPI had a 10 times lower risk to develop enlargement of the fistula and the complications that derive from it [23]. Similar results were reported by the teams led by Cocuzza [24] and Pattani [25] the difference being that this paper took into consideration radiotherapywhich was demonstrated to be another independent risk factor in developing complications of tracheoesophageal speech rehabilitation.…”
Section: Resultssupporting
confidence: 80%
“…Precisely, pathological supraesophageal reflux correlates with the onset of fistula complications and the consecutive rehabilitation degree, inducing the onset of periprosthetic leakage [ 26 ]. In this regard, Lorenz et al found higher VHI scores (up to 64.1 ± 9.6) with reflux severity ( p = 0.025) and total quality of life scores were worse in patients with highly pathological reflux ( p = 0.007).…”
Section: Discussionmentioning
confidence: 99%